Analysis of the supply of international technical assistance to the Armed Forces of Ukraine - Hannenko, Yury; Patsenko, Stepan (Social Development and Security, 2024)
Purpose: there is an analysis of the supply of international technical assistance to the Armed Forces of Ukraine. Method: the main methods of research are the method of analysis and comparison, the normative method. Practical implications:the analysis of the supply of international technical assistance to the Armed Forces of Ukraine shows that international technical assistance is a key element of ensuring national security and developing Ukraine’s logistical capabilities. This article analyzes in detail the main aspects of international technical assistance provided to the country, including its scope, directions and impact. The knowledge gained during the research determines the effectiveness and problems of supply, and also provides recommendations for its further improvement. International technical assistance significantly improves the logistical capabilities of the Armed Forces of Ukraine, providing them with high standards and resistance to modern threats. The article, based on the analysis of the supply of international technical assistance to the Armed Forces of Ukraine, reveals both positive and negative challenges facing this system. Value: ecommendations developed on the basis of the analysis can contribute to the optimization and improvement of the national security system and responses to modern challenges. Formulated directions for further research on improving the supply of international technical assistance to the Armed Forces of Ukraine. Future research: formulated directions for further research on improving the supply of international technical assistance to the Armed Forces.